Ensemble evaluation and projection of climate extremes in China using RMIP models. (24th October 2017) - Niu, Xiaorui; Wang, Shuyu; Tang, Jianping; Lee, Dong‐Kyou; Gutowski, William; Dairaku, Koji; McGregor, John; Katzfey, Jack; Gao, Xuejie; Wu, Jia; Hong, Song‐you; Wang, Yuqing; et al.
ABSTRACT: Under the framework of the Regional Climate Model Intercomparison Project (RMIP III), simulation results from six regional climate models (RCMs) and two global climate models (GCMs) were used to generate climate extreme indices for the present and future over China using two ensemble methods. All the models reasonably captured the observed climate extremes, and performance‐based ensemble averaging (PEA) outperformed the individual model and equal‐weighted averaging (MME) for the control climate. However, noticeable cold deficiencies in temperature extremes were found over areas with complex topography, and too frequent heavy precipitation at smaller intensities was simulated using the multiple model ensembles. Under the A1B scenario for 2041–2060, widespread increases in the 90th percentiles of the maximum temperatures (Tmax90p) and the 10th percentile of the minimum temperatures (Tmin10p) were projected, with larger increases in winter than in summer. Greater intensities in precipitation extremes were projected over China, with the exception of Inner Mongolia. Large uncertainties exist in the projected mean diurnal temperature range (Trange), number of days with precipitation exceeding 10 mm (R10) and the maximum number of consecutive dry days (CDD) because of disagreements in both the magnitudes and signs of the climate model projections, and even the two ensemble methods presented opposite signs over some regions. Abstract : Under the A1B scenario for 2041–2060, widespread increases in the Tmax90p and Tmin10p are projected by multi‐model ensembles over China. Greater intensities in precipitation extremes are projected over China, with the exception of Inner Mongolia. Large uncertainties exist in the projected mean Trange, R10 and CDD.